Benthic-Pelagic Coupling of Marine Primary Producers Under Different Natural and Human-Induced Pressures’ Regimes - Gerakaris, Vasilis; Varkitzi, Ioanna; Orlando-Bonaca, Martina; Kikaki, Katerina; Mozetič, Patricija; Lardi, Polytimi-Ioli; Tsiamis, Konstantinos; Francé, Janja (Frontiers in Marine Science, 2022)
Marine primary producers are highly sensitive to environmental deterioration caused by natural and human-induced stressors. Following the Water Framework Directive and the Marine Strategy Framework Directive requirements, the importance of using the different primary producers of the coastal marine ecosystem (pelagic: phytoplankton and benthic: macroalgae and angiosperms) as appropriate tools for an integrated assessment of the ecological status of the coastal environment has been recognized. However, the processes by which water column characteristics and phytobenthic indicators are linked have not been systematically studied. Based on a large dataset from three Mediterranean sub-basins (Adriatic, Ionian and Aegean Seas) with different trophic conditions, this study aims to explore the coupled responses of benthic and pelagic primary producers to eutrophication pressures on a large scale, focusing on the structural and functional traits of benthic macroalgal and angiosperm communities, and to investigate the key drivers among the different eutrophication-related pelagic indicators (such as nutrient and Chl-a concentrations, water transparency, etc.) that can force the benthic system indicators to low ecological quality levels. In addition to the effects of high nutrient loading on phytoplankton biomass, our results also show that increased nutrient concentrations in seawater have a similar effect on macroalgal communities. Indeed, increasing nutrient concentrations lead to increased coverage of opportunistic macroalgal species at the expense of canopy-forming species. Most structural traits of Posidonia oceanica (expressed either as individual metrics: shoot density, lower limit depth and lower limit type, or in the context of PREI index) show opposite trends to increasing levels of pressure indicators such as ammonium, nitrate, phosphate, Chl-a and light attenuation. Furthermore, our results highlight the regulating effect of light availability on the ecological status of seagrass meadows (Posidonia oceanica and Cymodocea nodosa). Increasing leaf length values of C. nodosa are closely associated with higher turbidity values linked to higher phytoplankton biomass (expressed as Chl-a). Overall, the coupling of pelagic and benthic primary producers showed consistent patterns across trophic gradients at the subregional scale.